Supervisi Kepala Sekolah Kepada Guru Dan Tenaga Kependidikan Melalui Gaya Komunikasi Yang Baik Di Madrasah - Su'udin Aziz; Farida Isroani (Pusat Riset dan Inovasi Nasional, 2022)
Supervision is an important instrument insupporting theachievementof educational goals. Supervision or supervision carried out at the madrasah level is the responsibility of a madrasah head. The communication style of the head of the madrasah when supervising education personnel has an impact on improving the performance of education staff. This article discusses the communication style of the head of the madrasah in supervising education personnel. Supervise the head of the madrasah how his efforts are in optimizing the potential of existing educators. This discussion is the result of research conducted. Qualitative research with results showing that the supervision model carried out by the head of the madrasah when supervising teachers with interpersonal communication style carried out by the head of the madrasah is able to motivate teachers and education staff to develop their capacity. Where the head of the madrasah observes directly the ongoing learning process in the supervised classroom while approaching it with an interpersonal communication style. This is done so that the head of the madrasah knows the readiness and preparation of teachers in the learning process. From here the head of the madrasah will follow up as needed to optimize the potential of teachers and education staff respectively.